Dark triad and cyber aggression among Chinese adolescents during COVID-19: A moderated mediation model - Zhang, Zhen; Bian, Shengnan; Zhao, Hui; Qi, Chunhui (Frontiers in Psychology, 2022)
During the COVID-19 pandemic, the use of online learning has become a necessary choice for students, and would increase the probability of cyber aggression. Despite the relationship between Dark Triad and cyber aggression previous was explored in previous research, the underlying psychological mechanism of cyber aggression in adolescents is still unclear. The current study aimed to examine the mediating role of moral disengagement and the moderating of gender in the relationship between Dark Triad and cyber aggression. A sample consists of 501 Chinese adolescents (246 females; 255 males) between the ages of 11 20. Participants completed the Dirty Dozen Scale, Moral Disengagement Scale, and Cyber Aggressive Behavior Scale. Results show that higher levels of dark personality were associated with higher levels of moral disengagement and cyber aggression. Moral disengagement partially mediated this positive effects of dark personality on cyber aggression. Moreover, gender moderated the mediation model. Specially, the positive relationship between dark triad personality and cyber aggression was stronger among females adolescents. These findings advance the understanding of how dark triad personality induces Chinese adolescents’ cyber aggressive behavior.